Avian Responses to Different Grazing Management Practices in Neotropical Temperate Grasslands: A Meta-Analysis - Facundo Niklison; David Bilenca; Mariano Codesido (Birds)
Bird populations inhabiting the Rio de la Plata Grasslands in southern Brazil, Argentina, and Uruguay are known to be affected by livestock grazing practices. Cattle grazing can lead to changes in bird assemblages by affecting the heterogeneity of vegetation structures. We conducted a meta-analysis using studies that reported bird richness and abundance under different grazing management practices. We compared ranches under continuous grazing management (control, CGM) to (1) ranches under technological inputs management (TIM, herbicides and exotic pastures) and (2) ranches under ecological process-based management (EPM), which include ranches that utilise controlled and rotational grazing. We used random effects multilevel linear models to evaluate grazing regimen impacts. Our results indicate a negative impact of TIM on both bird abundance and richness (mean ± SE: −0.25 ± 0.07 and −0.92 ± 0.10, respectively) since the use of inputs simplifies vegetation structure and results in the loss of ecological niches. Compared to CGM, the influence of EPM on total bird abundance appears to be more dependent on grassland height, as evidenced by a decline in short grasses and increase in tall grasses. Our meta-analysis suggests that EPM practices may be beneficial for the conservation of endangered tall-grass birds.